Family Values in Various Cultures: Linguoculturological and Conceptual Analysis - Nuritdinova, Shoira Xamidovna (TLEP – International Journal of Multidiscipline, 2026)
This article examines the concept of family values from a linguocultural perspective, focusing on its semantic, cultural, and conceptual dimensions across different languages and cultures. The study is based on the theoretical foundations of linguoculturology, as developed by E. M. Vereshchagin, V. G. Kostomarov, and further expanded by Yuri Karaulov and Anna Wierzbicka. Special attention is given to the concept of “family” as a culturally marked unit reflecting national mentality, social norms, and value systems. The article analyzes the structure of the concept, including its lexical, associative, and etymological layers, and highlights cross-cultural differences between Eastern and Western interpretations of family values. The findings demonstrate that language serves as a key medium for encoding and transmitting culturally specific models of family relations, moral obligations, and social expectations. The research contributes to a deeper understanding of the interrelation between language, culture and cognition.